Capturing student learning with thematic analysis - JEFFREY R. MUELLER (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This paper examines the best methods for employing thematic analysis to determine what 118 students in eleven distinct online teambuilding courses taken as part of an undergraduate management curriculum in 20112013 learned. There is a brief discussion of accrediting organizations, a critique of their assessment methods, and some suggestions for using thematic analysis more frequently as a primary or secondary indicator of student learning.Methodology: All 11 classes in this sample were taught by the same professor at National University in California, USA (the author).Findings: The primary findings of this study are that students who took a course in teamwork benefited greatly from learning the importance of writing a team agreement at the outset of a team assignment, as well as from conducting confidential peer ratings at the assignment’s conclusion.Implications/Novelty: The use of thematic analysis as a supplementary tool to the official, university-driven end-of-course exams may prove fruitful for some educators. Suggestions are made for further research and for popularizing the use of thematic analysis.